Understanding Creative Behavior Among Indonesian Radio Station Managers: A Conceptual Framework - J. Setiadi, Nugroho (Jurnal Riset Ekonomi dan Bisnis, 2009)
The main purpose of the article is to increase understanding in some personal characteristics affecting creative performance among Indonesian radio station managers’ leadership context. Organizational researchers and managers alike have long held the view that individual creativity is critical for organizational success. The first element of improvement creativity, that is, the ‘person’, is obvious. New ideas are not generated or implemented by organizations or technology, but come into being through efforts of dedicated people. Thus, it is important to understand people’s personality, motivations, skills, level of experiences, and psychological preferences. A number of propositions for future research in relational of individual creativity model are also suggested.Keywords: Creativity, Personal Characteristics, Motivation